Predictive maximal heart rate equations in child and adolescent athletes: a systematic review - Anderson Sartor Pedroni; Aniuska Schiavo; Eléia de Macedo; Natália E de Campos; Aline Dill Winck; João Paulo Heinzmann-Filho (Editora Champagnat, 2018)
Abstract Introduction: The maximal heart rate (HRmax) is considered the highest value of HR achieved during a physical effort close to exhaustion. Objective: To evaluate the applicability of the predictive HRmax equations during exercise tests in child and adolescent athletes through a systematic review. Methods: It is a systematic review, through Scopus, Pubmed, Lilacs, Scielo and PEDro. The included studies compared the measured and estimated HRmax predictive equations during exercise tests in child and adolescent athletes. The following search strategy was used: "Exercise test OR Exercise testing OR Cardiopulmonary exercise test OR Cardiopulmonary exercise testing OR Peak oxygen uptake OR Maximal oxygen consumption OR Exercise capacity OR Heart rate OR Heart rate OR Pulse rate OR Pulse rates OR Heart rate control OR Cardiac chronotropic OR Predictive value test AND Predictive equations". Results: From a total of 1,664 articles, only 4 were included. All compared the measured HRmax values with those estimated by the "220 - age" equation; 3 used the formula "208 - (0.7 x age)", and only 1 used the "223 - (1.44 x age)" equation. Although all of them stated that the "220 - age" equation overestimates HRmax, the formula "208 - (0.7 x age") underestimated (2 articles) and overestimated (1 study) the measured results, while the equation "213 - (1.44 x age) was also not adequate. Conclusion: The use of predictive HRmax equations for child and adolescent athletes does not seem to be recommended. The use of cohort points for these estimates is carefully recommended.